SHE-AI PRENEUR: EMPOWERING WOMEN MSME ENTREPRENEURS THROUGH ARTIFICIAL INTELLIGENCE TRAINING FOR DIGITAL MARKETING AND SUSTAINABLE BUSINESS NETWORKING - Mutoharoh Mutoharoh; M. Syadeli Hanafi; Dethia Hs Suci Nurani; Ramdan Ramdan; Anton Nasrullah; Sasithorn Suwandee (Yayasan Education and Social Center, 2025)
Digital transformation presents opportunities for womenled micro, small, and medium enterprises (MSMEs) but persistent gaps in AI literacy and networked collaboration limit their competitiveness. Prior empowerment programs emphasized basic digital skills without integrating Artificial Intelligence (AI) as a core marketing instrument or fostering sustainable business networks. This study evaluated the SHEAI Preneur intervention designed to increase AI literacy, AIbased digital marketing competence, content production quality, and business networking among women MSME entrepreneurs in Serang Regency, Indonesia. A threemonth participatory program was implemented with 30 purposively sampled women entrepreneurs; the mixedmethods evaluation employed pre and posttests, structured surveys, observation checklists, semistructured interviews, and activity documentation. Quantitative data were analyzed using descriptive statistics and percentage change of competency scores, while qualitative data underwent thematic analysis. The results showed marked improvements across all measured domains: AI literacy, digital marketing skills, content creation, and business networking increased substantially after the intervention, attendance and engagement rates were high, and participants produced AIgenerated promotional materials independently. The program also yielded emergent collaborative practices and a sustained digital community for ongoing exchange. Theoretically, the study advances empowerment and digital transformation frameworks by demonstrating how practicebased AI training plus mentoring and network formation convert digital skills into applied entrepreneurial capacity. Practically, the SHEAI Preneur model offers a scalable template for inclusive AI adoption among women MSMEs, with implications for policy, incubator design, and future longitudinal impact assessments.